Von Höfler vagyok, Werther variáció I - II
A glimpse into the intricate and fascinating fates of the generations of the great Pécs leather manufacturing family via the archival footage and accounts of Tibor Von Höfler. A double tale with faded images bearing witness to the 250-year saga of the Hungarian von Höfler family - an elegy for the last member of the family. Researchers have recently claimed that Goethe modeled his famous Werther on one of Tibor Höfler’s ancestors: this film presents itself in time and space with this double twist. Though Goethe's hero Werther is quite different from the real 18th-century Jakob von Höfler, the threads of the old and new legends of the Höfler saga intertwine in a double spiral of destiny within the turmoil of 20th century Central Europe. The real and invisible images of the melancholic hero, Werther - a literary destiny - intersect with those of the real life protagonist. Von Höfler's life, love, family, and fate. Péter Forgács